Multi-Stakeholder Innovation in Tourism Industry: A Recent Development and Future Directions - Poetry, Roma Nova Cahjati; Simatupang, Togar Mangihut; Ghazali, Achmad (The Asian Journal of Technology Management (AJTM), 2021)
Abstract: Tourism is the most affected industry due to the Covid-19 pandemic, though it can be reinstated through innovations and collaborations. For instance, the marketing paradigm has shifted from product to service-dominant logic, influencing open innovations. The closed innovations are ineffective in the current business environment because of excluding other actors, such as suppliers, universities, research organizations, public institutes, competitors, and tourists, specifically during the pandemic. This indicates stakeholder networks are essential in promoting tourism industry innovations. Therefore, this research examined the existing literature on multi-stakeholder innovation in the tourism industry. The relevant articles were identified using multiple keywords search on major research databases and analyzed based on tourism innovation research stream, type, and characteristic of innovation (value creation-value capture), innovation platforms, research methodology, the network actors, and key concepts. After identifying the gap, relevant literature for academicians and practitioners was provided. The literature is expected to guide practitioners on the importance of stakeholder innovations to restore and improve tourism conditions from the pandemic.Keywords: Literature review, Future direction, Innovation, Collaboration, Multi-stakeholder, Tourism industry